Psychoeducation of higher education seekers with using of the resource-oriented model of stress resiliency in war conditions - V.V. Ogorenko; A.E. Nikolenko; T.Y. Shusterman; V.O. Kokashynskyi; A.B. Khotimska; M.H. Koren (Medičnì Perspektivi)
The article presents the study results of resiliency modalities and the content of psychoeducational measures for higher education seekers in war conditions. The purpose of the study was to increase the effectiveness and to balance resiliency modalities use by higher education seekers in war conditions while using psycho-educational measures. 174 seekers of higher education were examined, including 144 students of the 4th-6th year of the medical faculty and the faculty of medicine and pharmacy of the Dnipro State Medical University, specializing in 222 «Medicine» (main group) and 30 students of the 4th-5th year of the metallurgical and electro-metallurgical faculties of the Ukrainian State University of Science and Technology (comparison group). A psychodiagnostic method using the resource-oriented model of stress resiliency "BASIC Ph" was employed. The first stage involved a statistical analysis of resiliency modalities and their average scores in both groups. In all participants of the main group, it was found that the highest average score was registered in the resiliency modality “Cognitive strategy”. The lowest score was observed for the “Social support” modality. In all participants of the comparison group, it was found that the “Cognitive strategy” modality, as in the main group, had a clear advantage over other modalities, and the lowest score was already observed for the “Emotions” modality. These results formed the basis for creating psychoeducational measures for stress resiliency among higher education seekers in wartime. Psychoeducation for higher education seekers was conducted from September to November 2023, including lectures and individual conversations upon request. The «BASIC Ph» model of stress resiliency was utilized as a framework for determining optimal human resource utilization during crises, with six modalities forming individual style of resiliency. It is crucial to identify dominant modalities and develop those that are less effective. The identified stress resiliency modalities provided a conceptual basis for developing of psychoeducational measures to enhance their effective and balanced use in war situations among higher education seekers. During psychoeducational work with higher education seekers, their resiliency models were analyzed, interpreted, and balanced. Study results should be taken into account in psychological support efforts for higher education seekers in war and post-war time.